The Influence of Polyvinyl Pyrrolidone (PVP) on Piroxicam Absorption with Everted Intestinal SAC Method - Fea Prihapsara; Anif Nur Artanti; Mimiek Murrukmihadi (Universitas Ahmad Dahlan, 2015)
Oral drug absorption was highly influenced by dissolution rate, especially for poorly and insoluble drugs. Piroxicam is a nonsteroidal anti-inflammatory drug that is practically insoluble in water. The oral absorption rate of piroxicam is dependent on its dissolution rate in the GI tract. Polyvinyl Pyrrolidone (PVP) as surfactant can increase drug solubility by means of a micelle forming mechanism. The aim of the study was to know the influence of addition and variation of Polyvinyl Pyrrolidone (PVP) on Piroxicam absorption with everted intestinal sac method. The concentration of piroxicam solution was prepared by PVP in 1.0,2.0 and 3.0 % respectively. Crane and Wilson tube containing 75 ml of themucosal fluid was taken at 37 0 C in waterbath. Than, serosal solution of 1.5 mlwas added to intestinal sac by turned upside down and tied to a cannula, then put into the tube containing the mucosal fluid and constantly flowing oxygen gas.Serosal solution of 1 ml were taken every 15 minutes and then diluted with 2 ml of Ba (OH) 2 and 2 ml of ZnSO4 then centrifuge until 25 minute. The absorbant of supernatant was measured by UV spectrophotometer and data analyse wascalculated by one-way ANAVA. PVP at 1%,2% and 3% increased piroxicamabsorption from the phosphate buffer pH 7.5 compared with negative control.According to P app , the values were 2.52 ± 0.43 cm/minute (negative control), 3.41 ± 2.17 cm/minute (1% PVP), 2.75± 1.14 cm/minute (2% PVP) and 4.77 ± 4.93 cm/minute (3% PVP) respectively. In conclusion. Lower doses of the surfactant (1%, 2%, and 3% PVP) significantly increased absorption of the drug by altering the membrane permeability.